2014
DOI: 10.1093/intqhc/mzu054
|View full text |Cite
|
Sign up to set email alerts
|

Does stewardship make a difference in the quality of care? Evidence from clinics and pharmacies in Kenya and Ghana

Abstract: Government stewardship appears to have some cumulative association with quality for clinics, suggesting that comprehensive engagement with providers may influence quality. However, our research indicates that continued medical education (CME) by itself is not associated with improved care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Trauma care vignettes for assessing care quality in LMICs is novel, however, they have been increasingly employed for other conditions. These include TB care in India [32,43], obstetric and newborn care in Ghana and Bangladesh [31,42] and diarrhoea in Kenya, Ghana and India [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trauma care vignettes for assessing care quality in LMICs is novel, however, they have been increasingly employed for other conditions. These include TB care in India [32,43], obstetric and newborn care in Ghana and Bangladesh [31,42] and diarrhoea in Kenya, Ghana and India [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Vignettes have also been used to gauge patient expectations of poor quality care (anchoring) [46] in health system care quality research studies. As in our study, scenarios are commonly developed from and scored against corresponding best practice guidance [31,42,45]. Some vignettes only reveal clinical findings when specifically requested by the provider [43], whilst others provide all required information within the scenario [17,42,45] whether or not specifically requested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this project used a vignette-based design with online panel samples. Although numerous cross-cultural studies have successfully used scenarios, 103,104 validation in a clinical setting should be considered. Fourth, recognizing that few studies have examined cross-cultural differences in AD decision making, samples representing Western individualist and Eastern collectivist cultures were used.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Recent studies have demonstrated that healthcare provider adherence to well-established clinical guidelines is poor across both the public and private sectors in numerous LMICs [2, 3, 4]. Suboptimal quality has been documented in both inpatient and outpatient settings, and has been attributed to multiple factors, including the environment of care (lack of necessary medications and fractured supply chain), insufficient and poorly trained healthcare providers, and lack of systems technology that supports adherence to best practices.…”
Section: Introductionmentioning
confidence: 99%